Student reaction to parallel hypertext and menu-based interfaces - A. J. Meadows; Mubarak Sulaiman; C. K. Ramaiah (Association for Learning Technology, 1993)
It is often necessary to consider the question of what sort of interface is most useful for retrieving information from a particular land of database. A small database of text-based but multi-faceted items is used here in order to compare ease and speed of retrieval from two commonly used combinations of interface - HyperCard on an Apple Macintosh and dBase III+ on a PC. For the restricted range of tasks employed here, the latter combination appears to be more acceptable to students with limited computer experience. However, in more general terms, the acceptability of an interface for information retrieval depends on what particular aspect of information retrieval is being emphasized, and what conceptual frameworks students bring to their tasks.